Hubungan Peran Keluarga Terhadap Tingkat Kepatuhan Pengobatan Pasien Hipertensi Di Puskesmas X Lampung Tengah - Sari, Cicih Ratna; Nurkhalika, Rachmi; Nofita, Nofita (Jurnal Ilmiah Wahana Pendidikan, 2024)
The prevalence of hypertension is increasing worldwide, according to the World Health Organization (WHO), but high blood pressure is still a health problem for a relatively large population. In 2015, there were around 1.13 billion people suffering from high blood pressure. Cases of hypertension are also increasing every year; it is estimated that in 2025, around 1.5 billion people will suffer from hypertension and around 9.4 million people will die from hypertension and its complications every year. The purpose of this study was to determine the relationship between the role of the family and the level of compliance of hypertensive patients in consuming anti-hypertensive drugs at the X Health Center in Central Lampung. This research method is a non-experimental study with a cross-sectional research design. The results showed that physical activity had a p-value of 0.000 (<0.05), which means it has a relationship with adherence to taking medication, and the role of the family had a p-value of 0.048 (<0.05), meaning there is a positive relationship between the role of the family and adherence to taking medication. significant.